2002
DOI: 10.1016/s0002-9440(10)62569-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary Thymic Extranodal Marginal-Zone B-Cell Lymphoma of Mucosa-Associated Lymphoid Tissue Type Exhibits Distinctive Clinicopathological and Molecular Features

Abstract: Extranodal marginal-zone B-cell lymphoma (MZBL) of mucosa-associated lymphoid tissue (MALT) arising in the thymus is rare, with the largest series in the literature including only three cases. In the present study, we investigated 15 cases of thymic MALT lymphoma to systematically characterize its clinical, histopathological, and molecular features. There was a marked female predilection (male:female ‫؍‬ 1:4), with a mean age of 55 years at diagnosis. There was a strong association with autoimmune disease, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 42 publications
6
106
2
1
Order By: Relevance
“…Long-term survival of patients with thymic MALT lymphoma after complete surgical resection without adjuvant chemotherapy or radiotherapy has been reported. 10) Because the oncologists did not recommend chemotherapy in the present case, the patient did not receive adjuvant chemotherapy. She was still alive without recurrence at the time of this writing (6 months postoperatively).…”
Section: Discussionmentioning
confidence: 91%
“…Long-term survival of patients with thymic MALT lymphoma after complete surgical resection without adjuvant chemotherapy or radiotherapy has been reported. 10) Because the oncologists did not recommend chemotherapy in the present case, the patient did not receive adjuvant chemotherapy. She was still alive without recurrence at the time of this writing (6 months postoperatively).…”
Section: Discussionmentioning
confidence: 91%
“…17 We have reported recently that VH3-23 and VH3-30 have been frequently used in thymic MALT lymphoma, a tumor closely associated with autoimmune disease. 18,26 Although the antigen specificity of antibodies encoded by VH3-23 and VH3-30 is currently unknown, it is suggested that B cells using these two VH fragments, which may be associated with H. pylori, are preferentially selected for MALT lymphomagenesis in the stomach. It has been controversial as to whether the majority of inflammation-dependent tumors progress to inflammationindependent tumors.…”
Section: Discussionmentioning
confidence: 99%
“…18,25,26 These primers have been used most commonly for VH gene analysis of malignant lymphoma. Subcloning of monoclonal PCR products was performed with pGEM T-easy vector (Promega, Madison, WI, USA) using DNA excised from the sharp rearrangement bands.…”
Section: Dna Extraction Vh Gene Amplification and Subcloningmentioning
confidence: 99%
“…Briefly, DNA extracted from paraffin sections was amplified by PCR with primers (FR2A, FR3A, LJH, and VLJH) to detect rearrangement occurring between framework regions and the joining region of the immunoglobulin heavy chain gene. 33,34 Amplification of a ␤-globin DNA fragment (268 bp) was used to indicate satisfactory preservation of DNA in the sample. Monotypic immunoglobulin light chain was detected by immunohistochemistry for and light chains.…”
Section: Case Selectionmentioning
confidence: 99%